Case Report: Covid-19 in Multiple Sclerosis Patients Treated With Ocrelizumab: A Case Series - De Mercanti, Stefania F.; Vercellino, Marco; Bosa, Chiara; Alteno, Anastasia; Schillaci, Valentina; Clerico, Marinella; Cavalla, Paola (Frontiers in Neurology, 2021)
Introduction: Limited data are available on the course of Coronavirus disease 2019 (COVID-19) in people with Multiple Sclerosis (MS). More real-world data are needed to help the MS community to manage MS treatment properly. In particular, it is important to understand the impact of immunosuppressive therapies used to treat MS on the outcome of COVID-19. Methods: We retrospectively collected data on all confirmed cases of COVID-19 in MS patients treated with ocrelizumab, followed in two MS Centers based in University Hospitals in Northern Italy from February 2020 to June 2021. Results: We identified 15 MS patients treated with ocrelizumab with confirmed COVID-19 (mean age, 50.47 ± 9.1 years; median EDSS, 3.0; range 1.0–7.0). Of these, 14 were confirmed by nasal swab and 1 was confirmed by a serological test. COVID-19 severity was mild to moderate in the majority of patients (n = 11, 73.3%; mean age, 49.73; median EDSS 3.0). Four patients (26.7%; mean age, 52.5 years; median EDSS, 6) had severe disease and were hospitalized; one of them died (age 50, EDSS 6.0, no other comorbidities). None of them had underlying respiratory comorbidities. Conclusion: This case series highlights the large variability of the course of COVID-19 in ocrelizumab-treated MS patients. The challenges encountered by the healthcare system in the early phase of the COVID-19 pandemic might have contributed to the case fatality ratio observed in this series. Higher MS-related disability was associated with a more severe COVID-19 course.